Presidential Diplomacy and Foreign Policy: The Governments of Milei and Lula in Argentina and Brazil - Frenkel, Alejandro (2026)
Both Luiz Inácio Lula da Silva in Brazil and Javier Milei in Argentina propose a reorientation of international strategy, although with markedly different visions and objectives. We use a comparative approach and a methodology with qualitative and quantitative indicators, focusing on the use of presidential diplomacy to analyze the foreign policy preferences of both presidents. We argue that Lula is committed to reestablishing ties with the Global South and shaping a multipolar world through active presidential diplomacy. Milei’s foreign policy, on the other hand, is characterized by a folding to the United States hegemony and a lack of interest in Latin American integration. It is also distinguished by the use of a type of diplomacy that we call “para-governmental.” That is, a diplomacy that prioritizes partisan actions and meetings with private sector actors without abandoning the President’s role, instead of governmental-level relations.